New records and an annotated checklist of the thick-headed flies from Algeria (Conopidae, Brachycera, Diptera) - Magdi S. A. El-Hawagry; Belkacem A. Boulaouad; Ahmed M. Soliman; Ayman M. Ebrahim; Hathal M. Al Dhafer (Egyptian Journal of Biological Pest Control, 2022)
Abstract Background The Conopidae are an interesting family of small- to large-sized endoparasitic flies, commonly known as thick-headed flies. These flies have been proposed as potential biological control agents of invasive social wasps (subfamilies: Polistinae and Vespinae, family: Vespidae). Results All known Algerian thick-headed flies (family Conopidae) are listed in the present study. Four subfamilies, nine genera and 23 species were treated. Three of these species are recorded herein from Algeria for the first time, namely Myopa pellucida (Robineau-Desvoidy), M. picta Panzer and Thecophora fulvipes (Robineau-Desvoidy). As far as they are known, Algerian localities and collection dates are provided, which comprise some new locality records. The data for this study were compiled from both available literature and material collected from some Algerian localities. Conclusion The family Conopidae (thick-headed flies) is hitherto represented in Algeria by four subfamilies, nine genera and 23 species. Three of these species are recorded herein for the first time.